Do Lactation-Induced Changes in Ghrelin, Glucagon-Like Peptide-1, and Peptide YY Influence Appetite and Body Weight Regulation during the First Postpartum Year? - D. Enette Larson-Meyer; Jessica Schueler; Erin Kyle; Kathleen J. Austin; Ann Marie Hart; Brenda M. Alexander (Journal of Obesity)
To determine whether fasting and meal-induced appetite-regulating hormones are altered during lactation and associated with body weight retention after childbearing, we studied 24 exclusively breastfeeding women (BMI = 25.2 ± 3.6 kg/m2) at 4-5 weeks postpartum and 20 never-pregnant controls (BMI = 24.0 ± 3.1 kg/m2). Ghrelin, PYY, GLP-1, and appetite ratings were measured before/and 150 minutes after a standardized breakfast and 60 minutes after an ad libitum lunch. Body weight/composition were measured at 6 and 12 months. Fasting and area under-the-curve responses for appetite-regulating hormones did not differ between lactating and control groups; ghrelinacyl, however, tended to track higher after the standardized breakfast in lactating women and was higher (p<0.05) after the ad libitum lunch despite a 24% higher energy intake (p < 0.05). By 12 months, lactating women lost 5.3 ± 2.2 kg (n=18), whereas control women (n=15) remained weight stable (p=0.019); fifteen of the lactating women returned to within ±2.0 kg of prepregnancy weight but three retained >6.0 kg. The retainers had greater (p<0.05) postmeal ghrelin rebound responses following breakfast. Overall these studies do not support the hypothesis that appetite-regulating hormones are altered during lactation and associated with postpartum weight retention. Altered ghrelin responses, however, deserve further exploration.